A vida como ela é.... nas mídias - Vitorello, Daniel Migliani (2006)
This dissertation explores the understanding of the communicative mechanisms between a creator, his production and the mass culture. Knowing communication not only as an objective dialogue. It was observed that there is, besides what is manifesto or showed explicitly, another level that is suggested or that communicates in an explicit manner. The main aim of this research was to understand what kind of communication was possible to be seen between the social imaginary and the work, from a characteristic that would show, on one hand the writer and what is extracted from the work, and on the other hand each character that is in contact with it.Therefore, the characteristic that supports this communication was analyzed, having as the corpus of this research, the serie A Vida como ela é... by Nelson Rodrigues, the texts are semi-fictional and they were published at first in the newspaper and then turned out to be stories on TV. This work was chosen because it was a huge success in Brazil, not only because of its content, sometimes obscene, but also because of its spread in different kinds of media, building up an interesting intersemiotic relation. For this reason, it was possible to construct a theoretical system around the communicative processes between the creator, the work and culture. The theoretical background comes from the following areas of knowledge: semiotic, the communication and information theories, the media, the theories of language, the studies about mediations , the media culture and psychoanalysis